UTILIZATION OF COMMUNICATION TECHNOLOGY TO IMPROVE THE EFFECTIVENESS OF PUBLIC RELATIONS MANAGEMENT - Arifatul Hasanah; Fitriani; Muhyidin; Ach. Nurfuad Al-Fajri; Multazem Aji Busono (Managere: Indonesian Journal of Educational Management, 2024)
This research focuses on the implementation of communication technology in public relations management at SD Darut Thalabah Wonosari, with the aim to identify the impact of budget constraints and lack of technology skills among staff on the effectiveness of communication technology use and explore strategies to overcome these barriers. The research method used is qualitative with a descriptive approach. Data was collected through observation, interviews, and documentation at SD Darut Thalabah Wonosari, located at Jalan Kebon Agung No. 23, Wonosari, Gunungkidul Regency, Special Region of Yogyakarta. The results showed that although communication technologies such as instant messaging apps, email, and school web pages have improved communication efficiency, budget constraints and lack of technology skills are still major obstacles. The research also found that regular training and interactive website development can overcome most of these barriers. The implications of the study show the importance of adequate budget allocation and continuous training to improve the efficiency and effectiveness of technology-based public relations management in schools.